An evolutionary game analysis of incentive of industrial parks, government support and enterprise innovation willingness in China - Zhen, Jie; Ouyang, Juan; Wang, Lan (Heliyon, 2024)
Industrial parks are the important carriers to promote regional innovation and economic development. The policy preferences of the government, the support orientation of the industrial park and the innovation willingness of the enterprises in the park play a significant role in promoting the high-quality development of the industrial parks. In order to clarify the decision-making process of each subject, this paper constructs a triple evolutionary game model between the government, industrial park and enterprises in the park, Matlab software is used to conduct simulation research, and the strategy selection of each subject in the process of promoting high-quality development of the park is analyzed, as well as the influence of variables on the evolutionary game. Through numerical simulation, this study finds that the strategy choice of the government and the industrial park is influenced by the cost of innovation management for enterprises. In addition, the innovation willingness of enterprises is affected by the policy preference of the government and the support orientation of the industrial park, the excessive tax preference of the government will lead to negative innovation behaviors of the enterprises, the “inward incentives” support orientation of the industrial park can stimulate the enterprises’ innovation willingness on “active innovation”, the enterprises behavior of “active innovation” will strengthen the “inward incentives” support orientation of the industrial park in turn. The difference of the benefits and the costs between the two support orientations by the industrial park will lead to the equilibrium points stabilized at different strategy combinations. Based on these findings, countermeasures and suggestions are proposed in this study.